2017
DOI: 10.1177/1479972317719086
|View full text |Cite
|
Sign up to set email alerts
|

Assessing carer needs in chronic obstructive pulmonary disease

Abstract: Informal carers play a key role in supporting patients with chronic obstructive pulmonary disease (COPD), particularly when disease is advanced. They also enable delivery of healthcare professional advice. There is a well-established impact of the caring role on carers in both the generic and COPD-specific literature. The needs of carers of patients with COPD are both generic to the caring role and disease specific. Healthcare professionals and health systems supporting patients with COPD need to actively iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 73 publications
0
42
0
Order By: Relevance
“…Caregiver’s needs should be assessed systematically and in a formalised manner in healthcare settings. 16 When developing collaborative models of care the inclusion of caregivers is imperative. 100 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiver’s needs should be assessed systematically and in a formalised manner in healthcare settings. 16 When developing collaborative models of care the inclusion of caregivers is imperative. 100 …”
Section: Discussionmentioning
confidence: 99%
“… 15 Caregivers experience depressed mood, greater anxiety and increased subjective burden when their support needs are not met. 16 17 The unpredictability of HF and COPD leads to caregivers constantly adjusting their role, creating a need to continuously reassess what caregiver needs are. 18 19 Spousal caregivers of patients with myocardial infarction experience increased levels of stress, lifestyle impact and emotional distress.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by recent evidence demonstrating the substantial contribution of informal carers to people with advanced disease and chronic breathlessness, 35 including that their contribution saves approximately two-thirds of what would otherwise be formal care costs, 51 and the impact that this has on their own health and well-being. 51,181 Our participants also stressed the importance of education, both to increase awareness among the general public and health and social care professionals, and to upskill professionals within existing services. Multiple stakeholders suggested that breathlessness services should be developed by adapting existing services rather than introducing something new.…”
Section: For Policymentioning
confidence: 99%
“…31,38 Four included papers were review articles. 13,16,18,35 Quality appraisal Several issues were revealed through quality appraisal that may impact upon the validity of findings. Multiple studies encountered difficulties with recruitment and carer engagement, including Hynes et al 43 and Bove et al 33 Researchers suggested these issues may have arisen from the disparity between how some carers selfidentify and how they are labelled by others; researchers expressed concerns that the individuals they had attempted to recruit did not identify with the 'carer' label and hence chose not to engage with the studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…17 Identifying carers is the first step in this process, then a comprehensive, person-centred assessment should inform the provision of effective holistic support. 18 One intervention used for this purpose in practice is the Carer Support Needs Assessment Tool (CSNAT) Intervention. 14 The CSNAT Intervention comprises two components: (1) an evidence-based, 14 question tool that encompasses both direct and enabling needs which is integrated into (2) ‘The CSNAT Approach’, a five-stage person-centred process that facilitates a consistent and comprehensive assessment, response and review process.…”
Section: Introductionmentioning
confidence: 99%